(untitled) - Daniel, Wayne W. (Hoboken, NJ, 2013)
This Tenth Edition of Biostatistics maintains its predecessors’ comprehensive approach to biostatistics as it is used in the biological sciences. Successfully utilized by both statisticians and practitioners, Biostatistics is an algebra-based text geared towards the advanced undergraduate and graduate student. This new edition has been revised to more closely align with the modern practice of biostatics, teaching methods, and technologies.
Keywords: Medical statistics,Biometry,Thống kê y tế,Sinh trắc học